DO DECENT WORK AND ORGANIZATIONAL COMMITMENT REALLY AFFECT WORK ENGAGEMENT? AN EMPIRICAL STUDY OF EMPLOYEES IN INDONESIA - Dewi, Rina (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
Work engagement is an important issue for companies to gain support from their employees. This research aimed to analyze the impact of decent work and organizational commitment on Indonesian employees work engagement. Work engagement in Indonesia is generally quite good, indicated by an enthusiastic attitude and involvement in their work. However, there are still problems that need to be fixed to achieve opportunities for better improvements in the future. Social Exchange Theory (SET) was the source of work engagement and organizational commitment, while Psychology Work Theory (PWT) played an essential part in decent work. This research used both theories to analyze work engagement behavior. These three variables have never been applied simultaneously in behavioral analysis, especially in Indonesian employees. The total sample was 221 employees from various industries using a survey method by sending questionnaires. The result showed that decent work affected organizational commitment and work engagement, while organizational commitment affected work engagement. Moreover, organizational commitment acted as an intervening between the relationship of decent work to work engagement. This research provides a conceptual framework to comprehend factors that affect work engagement in developing countries, including Indonesia. Work engagement is related to employee well-being, which includes physical and mental well-being, as well as strong working relationships between the organization and employees. Strong working relationships are a solid foundation in building a work culture and competitive advantage, which ultimately drives the achievement of organizational goals with organizational support in decent work and efforts to build organizational commitment, especially affective organizational commitment and normative commitment.